2015
DOI: 10.1002/jssc.201500837
|View full text |Cite
|
Sign up to set email alerts
|

Multiresidue method for the simultaneous determination of 16 acaricides by modified quick, easy, cheap, effective, rugged, and safe extraction andultra-high performance liquid chromatography coupled with tandem mass spectrometry in citrus

Abstract: An ultra-high performance liquid chromatography coupled with tandem mass spectrometry analytical method was developed for simultaneously determining 16 acaricides in citrus based on an optimized quick, easy, cheap, effective, rugged, safe strategy. Good linearities of the standard curve of 5-1000 μg/kg was obtained with regression coefficients higher than 0.9967. Recoveries for all compounds ranged from 72 to 111% with relative standard deviations lower than 14.4% at spiked levels of 5, 50, and 500 μg/kg. Low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Related studies reported that the use of QuEChERS coupled with the HPLC-MS/MS method for the determination of multiresidues including fenbutatin oxide in plant-derived foods (citrus, pepper) achieved good results. 12 , 13 However, our method can be applied not only to the determination of fenbutatin oxide in plant-derived foods but also in animal-derived foods that are rich in fat, protein, and other lipophilic compounds.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Related studies reported that the use of QuEChERS coupled with the HPLC-MS/MS method for the determination of multiresidues including fenbutatin oxide in plant-derived foods (citrus, pepper) achieved good results. 12 , 13 However, our method can be applied not only to the determination of fenbutatin oxide in plant-derived foods but also in animal-derived foods that are rich in fat, protein, and other lipophilic compounds.…”
Section: Resultsmentioning
confidence: 99%
“… 8 11 To the best of our knowledge, there are only two existing reports that QuEChERS coupled with the HPLC-MS/MS method was used to determine multiresidues including fenbutatin oxide in plant samples, i.e., citrus and peppers. 12 , 13 However, no report is available on the determination of fenbutatin oxide residues in animal-derived foods. The obstacle may be due to the fact that they are rich in fat, protein, and other lipophilic compounds, which are easily coextracted with the target analytes.…”
Section: Introductionmentioning
confidence: 99%
“…After the widespread acceptance and application of the QuEChERS method , acetonitrile has become largely used to extract pesticide residues from agricultural and environmental matrices . Acetonitrile was shown to be the most advantageous solvent for extraction of pesticide residues from food samples and ethyl acetate was reported to be the second best .…”
Section: Resultsmentioning
confidence: 99%
“…N , N ‐Bis(2,4‐Dimethyliminomethyl) methylamine is a chemical called amitraz and a common organic nitrogen insecticide and acaricide mainly used to kill insects, cotton bollworms, aphids, and other pests on crops, such as vegetables, tea, and cotton [1,2]. Amitraz is less toxic to bees than other insecticides and widely used for controlling parasites in the hive to effectively prevent bee diseases caused by the Varroa destructor [3,4].…”
Section: Introductionmentioning
confidence: 99%